EVALUATING INDONESIAN LANGUAGE LEARNING IN INDONESIAN ISLAMIC HIGHER EDUCATION USING CIPP MODEL - Rahmiati, Rahmiati; Rasyid, Muhammad Nur Akbar (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
The primary objective of this study was to evaluate the implementation of Indonesian language learning in Indonesian Islamic higher education. To achieve this goal, the study employed the CIPP model and utilized a descriptive qualitative methodology. The collection of data was conducted by means of interviews, direct observation, and the examination of relevant documents. The findings are presented as follows: the program's alignment with stakeholder expectations is highly favorable in relation to the context component. Based on the available data pertaining to the utilization of learning resources for the purpose of composing academic papers and conducting research, the efficacy of the program's input is considered commendable. The program is commendable due to the inclusion of highly qualified lecturers, the provision of sufficient resources and infrastructure, and the utilization of standardized educational materials. The positive interaction between lecturers and students throughout the instructional and educational process is evidence that the process component is effective. The academic performance of students, with an average score of 3.64 out of 4.00, demonstrates how highly regarded the product component is. Overall, the implementation of Indonesian language learning is commendable, albeit with a few areas that require enhancement.